Ethical Moral Values & Indian Education System: Examining the Decline of Ethical Moral Values in the Indian Education System (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Morality Refers to personal or cultural value codes of conduct or social values. It is fact that morality play important role in an individual life as well as society, we learn moral values from family and education. These are the two important institutions, where we learn how to behave in a society. In the pre-independence era, when few people had access to formal education and it was known that educated persons would display civilized behavior, decency, good manners and ethical conduct, on the other hand, Uneducated persons would display uncivilized behavior and mostly crimes were committed by them. However, with a huge expansion of the education system, there is a marked decline in the characters, ethical moral values. Today most of the crimes are committed by students coming out of schools and colleges and well-educated people.Purpose –This report focuses on to understand the concept of Morality, Ethics and Education, on the possible causes of ethical deterioration i.e. corruption, privatization, etc. providing value-orientation is the only way to seize this decline in Indian educational system. In India, it is essential to increase ethical moral values, philosophical thinking, study, research and moral development in education system.Designmethodologyapproach –-The study was based on existing research and secondary data from various sources.